JORDAN STANGER-ROSS AND THE LANDSCAPES OF INJUSTICE RESEARCH COLLECTIVE. (Journal of American Ethnic History)
An introduction is provided to articles in the special issue on the theme of the injustice of selling the property of Japanese Canadians during their forced relocation to internment camps form 1942 through 1945.